2020
DOI: 10.1002/ptr.6733
|View full text |Cite
|
Sign up to set email alerts
|

Artemisia annua: Trials are needed for COVID‐19

Abstract: , an increasing number of cases of novel coronavirus, designated SARS-CoV-2, has caused worldwide outbreak of respiratory infection now termed coronavirus disease 2019

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 14 publications
0
27
0
2
Order By: Relevance
“…In 2015, the awarding of the Nobel Prize in Medicine for the discovery of artemisinin, a compound of plant origin found in Artemisia annua (annual mugwort), inspired the researchers to study the phytochemical and pharmacological properties of other species of the genus Artemisia . Recently, this species has been taken under consideration to be active toward the virus SARS-CoV-2 and disease COVID-19 [ 1 , 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…In 2015, the awarding of the Nobel Prize in Medicine for the discovery of artemisinin, a compound of plant origin found in Artemisia annua (annual mugwort), inspired the researchers to study the phytochemical and pharmacological properties of other species of the genus Artemisia . Recently, this species has been taken under consideration to be active toward the virus SARS-CoV-2 and disease COVID-19 [ 1 , 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, there is little scientific evidence of the effectiveness of such elixir and its extended consumption can have associated problems, the most important the development of resistance to the drug by the malaria parasites in a continent particularly sensitive to the disease. Nevertheless, there is evidence that the extract of Artemisia annua has antiviral properties, being active against SARS-CoV-1 ( Li et al., 2005 ), herpes simplex ( Karamoddini et al., 2011 ), hepatitis A ( Seo et al., 2017 ), hepatitis B, bovine viral diarrhoea, and Epstein-Barr ( Haq et al., 2020 ). This has stimulated the research of the potential use of artemisinin and derivatives (such as artesunate) to treat COVID19, which is now being conducted by several biotech companies (e.g., Mateon Therapeutics, ArtemiLife) as well as by public research institutions (e.g., the Liverpool School of Tropical Medicine, the Max Planck Institute of Colloids and Interfaces).…”
Section: What Plant-based and Plant-related Treatments Can Offer To Cmentioning
confidence: 99%
“…Besides malaria, Artemisinin and its derivatives have efficiency against some viral and parasitic diseases, i.e., hepatitis B, schistosomiasis, Chagas disease, African sleeping sickness, and treatment of some cancers (Duffy and Mutabingwa 2006;White 2008;Efferth 2007). In addition, recently, some research groups at the Max Planck Institute of Colloids and Interfaces in Germany (Gilmore et al 2020) and the University of Swat in Pakistan (Ul Haq et al 2020) have shown in laboratory studies that aqueous and ethanolic extracts of specially bred sweet wormwood plants (Artemisia annua) are active against the new coronavirus that has caused the COVID-19 pandemic. These studies motivate scientists again to pay attention to this miracle traditional medicinal plant.…”
Section: Introductionmentioning
confidence: 99%